Telaah Program Tahfidz Bagi Anak Usia Dini: Studi Kasus di RA Lukman Al Hakim Surabaya - Siswoyo; Aziziyah, Laili Ayu (Risda: Jurnal Pemikiran dan Pendidikan Islam, 2024)
Early Childhood Education in its standards is to train them to learn socially and maximize physical and psychological growth and development. Therefore, each playgroup and kindergarten also competes to create a superior program as an attraction and characteristic. RA Lukman Al Hakim is an early childhood education institution whose flagship program is tahfidz al-Qur'an. Because of these characteristics, this research aims to describe the tahfidz program implemented at RA Lukman Al Hakim and its methods. This research uses a case study type by maximizing observation as a data collection instrument. The results of this study concluded that RA Lukman Al Hakim only focused on memorizing juz 30 or juz 'amma and became a superior program that was distinctive compared to surrounding areas. Meanwhile, the Tahfidz learning methods at RA Lukman Al Hakim are very diverse but have not yet implemented media in teaching tahfidz.